After-Hours Pediatric Care Compared With Emergency Department Care: A Retrospective Charge Analysis. (April 2015) - Goodrich, Shea; Evans, Joseph; Gress, Todd; Werthammer, Joseph
Objective . To compare financial charges between children treated and released from an emergency department (ED) with those evaluated in an after-hours (AH) pediatric clinic. Methods . Medical records were retrospectively reviewed for 200 children <15 years of age treated in a hospital-based ED and compared with 200 children seen in an AH pediatric clinic. Our main outcome was median overall patient charges by clinic setting. We additionally examined charges by the 6 most common disease diagnoses. Results . Median charges for children treated and released from the ED were 457 [interquartile range (IQR) 320-628] compared with 140 (IQR 140-140) for those treated in the AH clinic ( P < .01). In addition, median charges were higher for the ED group in the 6 most common disease classes shared between the 2 study groups, both overall and for individual disease class comparison between study groups (all P < .01). We examined the association between charges and clinic setting in multiple quantile regression model while simultaneously adjusting for age, gender, insurance status, and diagnosis. Median costs were 305 (95% CI = 261 to 348; P < .01) more for the ED compared with the AH group. Conclusion . We found that financial charges for pediatric health care delivered in an AH clinic were less than those in an ED. We found significantly higher charges for the ED when like diagnoses were compared. Patients should be encouraged to attend AH clinics for urgent care needs when appropriate, which could result in significant cost savings to the health care system.